Automatic Humidity Monitoring System for Archive Preservation: Integration of Arduino with ISO 11799:2016 Standard - Rakha, Rakha Hafish Setiawan; Muhammad Shobaruddin; Endry Putra (Knowledge Garden: International Journal of Library Studies, 2025)
The preservation of archives in tropical regions faces critical challenges from uncontrolled humidity, leading to material degradation and information loss. Current monitoring systems lack real-time capabilities and remain cost-prohibitive, while the integration of automation with international preservation standards represents an unexplored solution, particularly in developing regions. This research aims to develop and evaluate an Arduino-based humidity monitoring system compliant with ISO 11799:2016 standards for paper archive preservation, offering an economical and accessible solution for archival institutions. The research employs a qualitative prototyping methodology, conducted at the Administration and Archives Gallery of Brawijaya University. Data collection involved systematic observation and literature review. The system utilizes Arduino Uno Rev 3, DHT11 sensor, LCD display, and alert modules, programmed to monitor humidity levels according to ISO standards. Analysis followed systematic procedures for data reduction, presentation, and conclusion drawing. The developed system successfully implemented three-level humidity classification with corresponding visual and audio notifications. Testing confirmed accurate detection and classification of humidity fluctuations across different thresholds (0% to ±2%, ±2% to ±5%, and >±5%), with appropriate system responses through LED indicators and audio alerts. The Arduino-based solution demonstrated effective integration with ISO 11799:2016 standards, providing real-time monitoring capabilities. The research validates the feasibility of implementing affordable Arduino-based monitoring systems for archive preservation that meet international standards. While showing promise in humidity monitoring and early warning capabilities, further development is needed for data storage integration and expanded monitoring range while adapting to ISO 11799:2024 standards.